Analisis Pengendalian Kualitas Pakan Ternak dengan Metode Six Sigma dan 5W + 1H - Agam Setianandha; Iqhbal Lilyan Syaputra; Rahmad Yusuf; Suseno Suseno (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The company CV. XYZ, located in Central Java, produces various types of animal feed according to the age of the consuming animals. However, there are quality issues with the pellet products they produce. Common problems include pellet color inconsistency, low density with ash content between 4-6% making the pellets prone to breaking, and pellet sizes not meeting industry standards, which should range between 0.3 to 0.5 cm. To reduce defects in animal feed production, the Six Sigma approach was applied to trace and identify the root causes and formulate improvement solutions. Data processed and Analyzed through control charts indicated that all values were within the upper and lower control limits, indicating that the process was statistically controlled and conformed to the standards set by the company. It was found that the average sigma value for Indonesian industrial companies is 2 to 3 sigma, while the sigma value at CV. XYZ reached 3.63. Although already above the industry average in Indonesia, CV. XYZ needs to continuously improve to meet the quality standards desired by consumers. Therefore, it is recommended to apply the 5W+1H method (What, Why, Where, When, Who, How) as a systematic approach to support continuous quality improvement.